Advances in omics technologies for traditional Chinese medicine in the prevention and treatment of metabolic bone diseases - Cai, Wenjun; Jiang, Lili; Zhao, Changwei; Zhou, Xiaoling (Frontiers in Pharmacology, 2025)
Metabolic bone disease (MBD), as one of the most severe metabolic disorders, remains a focal point and challenge in medical research. Numerous studies have demonstrated the efficacy of Traditional Chinese Medicine (TCM) in preventing and treating MBD. However, the inherent complexity of TCM metabolites poses significant limitations in elucidating their mechanisms of action. The advancement of omics technologies, including metabolomics, proteomics, and transcriptomics, has greatly facilitated research on MBD. These approaches enable the identification of potential biomarkers and the exploration of metabolic pathways and mechanisms underlying TCM interventions for MBD. Evidence indicates that TCM monomers, single botanical drugs, and herbal formulations are effective, safe, and well-tolerated in MBD prevention and treatment. This review summarizes recent applications and key findings of transcriptomics, proteomics, and metabolomics in studying the mechanisms of TCM interventions for MBD. It highlights the role of omics technologies in uncovering relevant metabolites and pathways under TCM treatment, providing valuable insights and clinical references for TCM-based strategies in managing MBD.